MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA DIMASA NEW NORMAL MELALUI E-MODUL INTERAKTIF (PIONIR: JURNAL PENDIDIKAN, 2021)
The low learning outcomes of students during the new normal period are generally influenced by school shifts and shortened study times. This study aims to improve the Students English learning outcomes of class VII A in MTsN 4 East Aceh in the new normal period through the Interactive E-module for the 2020/2021 Academic Year. This type of research is a Classroom Action Research which is conducted in two cycles. The research subjects were 30 grade students of class VII A MTsN 4 Aceh Timur. The data collection techniques used were observation, tests, questionnaires and documentation. The data analysis technique used is descriptive quantitative. The results of this study indicate that the use of the Interactive E-Module Media can improve the English learning outcomes of class VII A students of MTsN 4 Aceh Timur. The percentage of student learning outcomes increased, it can be seen from the test results in cycle I 70% to 86,67% in cycle II.